Politics of Law in Qanun Reformulation in Aceh: The Establishment of Wali Nanggroe Institution (UINSI Samarinda, 2021)
The Wali Nanggroe Institution is an authoritative religious local institution in Aceh, Indonesia. This Institution was found as a mandate from the Helsinki MoU and it was stated into Law No. 11 of 2006 concerning Aceh Governance which was later translated into Qanun No. 8 of 2012 concerning the Wali Nanggroe Institution. The establishment of Wali Nanggroe Institution brought some controversial issues in constitutional law in Indonesia, one of which is the requirement to become the institutional leader of Wali Nanggroe as regulated in the Qanun of the Wali Nanggroe Institution. This article will focus on the reformulation of the Qanun of the Wali Nanggroe Institution in Aceh by looking at political and legal aspects. This article is qualitative research with a non-doctrinal legal approach. The finding of this article indicates that the Qanun of the Wali Nanggroe Institution has been renewed twice. Nevertheless, there has been no significant renewal in the field of requirements to become an institutional leader of Wali Nanggroe. Summing up, this article reveals that the subordinates of the reform have not touched on substantive matters relating to the public interest, resulting in the absence of legal certainty for the people of Aceh. Keywords: Politics of Law, Qanun in Aceh, Wali Nanggroe Institution